2022
DOI: 10.1177/17588359221103206
|View full text |Cite
|
Sign up to set email alerts
|

Real-world experience with capmatinib in MET exon 14-mutated non-small cell lung cancer (RECAP): a retrospective analysis from an early access program

Abstract: Background: Patients with non-small cell lung cancer (NSCLC) presenting with mesenchymal–epithelial transition ( MET) exon 14 skipping mutation have an unfavorable prognosis with standard treatments. Capmatinib is a selective MET inhibitor, which showed promising efficacy in this patient population in early trials. Methods: We performed a retrospective, international, multicenter efficacy and safety analysis in patients with NSCLC treated with capmatinib in an early access program between March 2019 and Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
0
18
0
2
Order By: Relevance
“… 10 A recent real-world study on the early access program of capmatinib also reported intracranial RR of 46% and disease control rate of 91%, comparable with the previous phase 2 trial results. 21 These data suggest the possible CNS activity of the novel MET inhibitors. A current international guideline recommends capmatinib for MET exon 14-positive NSCLC patients with brain metastasis.…”
Section: Discussionmentioning
confidence: 85%
“… 10 A recent real-world study on the early access program of capmatinib also reported intracranial RR of 46% and disease control rate of 91%, comparable with the previous phase 2 trial results. 21 These data suggest the possible CNS activity of the novel MET inhibitors. A current international guideline recommends capmatinib for MET exon 14-positive NSCLC patients with brain metastasis.…”
Section: Discussionmentioning
confidence: 85%
“…In a preplanned analysis of Japanese patients enrolled in GEOMETRY mono-1 ( n = 45), peripheral edema was the second most frequent treatment-related AE, occurring in 31% of patients [ 25 ]. More recently, real-world data from an international early access program study of capmatinib in 81 patients with advanced METex14 -mutated NSCLC found that peripheral edema was the most common treatment-related AE of any grade (48%) or Grade ≥ 3 (13%) [ 26 ].…”
Section: Incidence Of Peripheral Edema In Clinical Trialsmentioning
confidence: 99%
“…More recently, real-world data from an international early access program study of capmatinib in 81 patients with advanced METex14 -mutated NSCLC found that peripheral edema was the most common treatment-related AE of any grade (48%) or Grade ≥ 3 (13%) [ 26 ].…”
Section: Incidence Of Peripheral Edema In Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their OS is comparable to that of patients with undetected major driver mutations ( 16 ). Although MET ex14-positive NSCLC patients treated with selective MET TKIs reported longer OS, up to 30%-40% of these patients were reported to be non-responders ( 11 , 17 , 18 ). The factors associated with a poor prognosis in these patients remain unclear.…”
Section: Introductionmentioning
confidence: 99%